Developing Student Worksheet Assisted with Geogebra on Derivative Materials. (February 2019) - Farida; Supriadi, N; Kurniawati, N
Abstract: This study aims to determine the feasibility and attractiveness of students' responses to the development of learning media in the form of student worksheets assisted with GeoGebra on the derivative material. This research was conducted using the Research & Development (R & D) method through the 4D development procedure proposed by Thiagarajan Sivasailam, which includes; 1). Define stage, 2). Design stage 3). Development stage, and 4). Dissemination stage. Data collection techniques used were validation questionnaire sheet. The instruments used were in the form of validation questionnaires to determine the feasibility of the student worksheets and questionnaire responses of students to find out the attractiveness. The data analysis technique used in research and development was quantitative descriptive to process the data in the form of scores from the evaluations by the validators and responses from the students. The qualitative descriptive was used to describe the data in the form of comments suggesting improvements from the validators. The results of student worksheets validation from material experts obtained an average value of 4.60 with very valid criteria. The results of student worksheets validation from media experts obtained an average value of 4.00 with valid criteria. The students' responses toward the developed learning media in small-group trials obtained an average value of 3.70 with attractive criteria and in the large-group trials obtained an average value of 3.75 with attractive criteria. This means that the learning media in the form of student worksheet assisted with GeoGebra in the derivative material is feasible and attractive.